2021
DOI: 10.37934/arfmts.83.1.3445
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Solutions of Hybrid Nanofluids Flow Via Free Convection Over a Solid Sphere

Abstract: The purpose of the existing study is to examine how heat transfer enables consolidated by variations in the basic advantages of fluids in the existence of free convection with the assistance of suspended hybrid nanofluids. Iron-graphene oxide suspended in water as a hybrid nanofluid flow on a solid sphere is also considered in this work. The partial differential equations are gotten, for this problem, by transforming the mathematical governing equations using similarity equations (stream function). These parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…() w ux is the velocity of the stretching surface with a being a positive constant, T  is the ambient temperature and s h is the heat transfer parameter. Under the assumption that water as the base fluid and nanoparticles are in thermal equilibrium and in a no-slip condition, the following nanofluid expressions are introduced [20,21].…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…() w ux is the velocity of the stretching surface with a being a positive constant, T  is the ambient temperature and s h is the heat transfer parameter. Under the assumption that water as the base fluid and nanoparticles are in thermal equilibrium and in a no-slip condition, the following nanofluid expressions are introduced [20,21].…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…is the conjugate parameter for Newtonian heating. The thermophysical properties of the chosen nanoparticles and base fluid can be found in Table 1 [20].…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…There are ternary hybrid nanofluid simulation models continually used to study the demeanor of nanofluids. The ternary hybrid nanofluids are considered an extension of nanofluid effects, which are characterized by their ability to efficiently heat transfer [21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that heat transfer enhancement increases by increasing of hybrid nanofluid volume concentration and volume flow rate. Recently, the study of hybrid nanofluids on flow over various situations was considered by researchers, such as over a vertical, solid sphere, stretching/shrinking sheet, bioconvection and others [8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%